R&D to go commercial - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
After more than a quarter of a century of intense research, the International Centre of Insect Physiology and Ecology (ICIPE), has developed a range of research and development (R&D) products for application in agriculture, livestock development and...